The Interplay of HIV and Autophagy in Early Infection - Cabrera-Rodríguez, Romina; Pérez-Yanes, Silvia; Estévez-Herrera, Judith; Márquez-Arce, Daniel; Cabrera, Cecilia; Espert, Lucile; Blanco, Julià; Valenzuela-Fernández, Agustín (Frontiers in Microbiology, 2021)
HIV/AIDS is still a global threat despite the notable efforts made by the scientific and health communities to understand viral infection, to design new drugs or to improve existing ones, as well as to develop advanced therapies and vaccine designs for functional cure and viral eradication. The identification and analysis of HIV-1 positive individuals that naturally control viral replication in the absence of antiretroviral treatment has provided clues about cellular processes that could interact with viral proteins and RNA and define subsequent viral replication and clinical progression. This is the case of autophagy, a degradative process that not only maintains cell homeostasis by recycling misfolded/old cellular elements to obtain nutrients, but is also relevant in the innate and adaptive immunity against viruses, such as HIV-1. Several studies suggest that early steps of HIV-1 infection, such as virus binding to CD4 or membrane fusion, allow the virus to modulate autophagy pathways preparing cells to be permissive for viral infection. Confirming this interplay, strategies based on autophagy modulation are able to inhibit early steps of HIV-1 infection. Moreover, autophagy dysregulation in late steps of the HIV-1 replication cycle may promote autophagic cell-death of CD4+ T cells or control of HIV-1 latency, likely contributing to disease progression and HIV persistence in infected individuals. In this scenario, understanding the molecular mechanisms underlying HIV/autophagy interplay may contribute to the development of new strategies to control HIV-1 replication. Therefore, the aim of this review is to summarize the knowledge of the interplay between autophagy and the early events of HIV-1 infection, and how autophagy modulation could impair or benefit HIV-1 infection and persistence, impacting viral pathogenesis, immune control of viral replication and clinical progression of HIV-1 infected patients.